Synthesis and Crystal Structure of [CuL]·(SCN)2 - Bi, Jian-Hong; Xia, Hong; Huang, Zi-Xiang (Asian Journal of Chemistry, 2011)
A new metal-organic complex [CuL]·(SCN)2 ( L = 5,5,7,12,12,14-hexamethyl-1,4,8,11- tetraazamacrocyclotetradecane·2ClO4) has been synthesized by the reaction of CuL with potassium thiocyanate and investigated by infrared spectrometry, elemental analysis and X-ray diffraction. The crystal belongs to monoclinic crystal system and has space group P2(1)/c with a = 7.6549(6) Å, b = 9.4174(8) Å, c = 16.3539 (16)Å. a = 90 º, b = 101.508(4)º, g = 90º, v = 1155.24(17)Å3, z = 2, Dc = 1.334Mg/m3, Mr = 464.19, F(000) = 494 and μ = 1.141 mm-1. The final R = 0.0861, wR = 0.2352 for 8186 observed reflections with I > 2s(I). In terms of the crystal structure, copper(II) ion is four-coordinated with four nitrogen atoms in the skeleton of tetraazamacrocyclotetradecane, showing a slightly distorted square geometry.